(untitled) (Bangladesh Journal of Agricultural Research, 2018)
The study was conducted in four districts namely Rajshahi, Chuadanga, Comilla and Rangpur during 2015-2016 to estimate the effect of drought in maize production, technical efficiency and adaptation strategy of maize farmers, and explore related problems of maize cultivation in the study areas.Rajshahi and Chuadanga were selected as drought prone areas whereas Rangpur and Comilla were selected as favorable environment. A total of 200 farmers taking 50 from each district were selected randomly for the study. Per hectare total cost of maize cultivation in drought prone areas was found Tk. 92,582, whereas in normal environment it was Tk. 79,594. Per hectare average yield in drought prone and normal areas were 7576 kg and 8729kg, respectively. Per hectare net return of maize in drought prone and normal areas were Tk. 28,062 and Tk. 59, 871, respectively.On full cost basis benefit cost ratio (BCR) in drought prone and normal areas were 1.31 and 1.75, respectively. Result of semi-logarithmic regression model indicated that maize production was decreased by 22.4 percent in drought prone areas than normal environment. Loss of yield (70%), loss of plant growth (55%) and problem in flowering stage (43%) were reported to be the major effects of drought.The major adaptation strategies in the drought prone areas were increase number of irrigation (77%), increase amount of fertilizer (42%) and seed (31%) and change of planting date (30%). Higher price of irrigation (70%), lack of drought tolerant variety (48%) and lack of quality seed (31%) were the major problem in drought prone areas. Again,disease infestation (64%), lack of quality seed (41%) and high price of seed (36%) were the major problem in normal environment. Scientists should take attempt to develop drought tolerant maize variety. Bangladesh J. Agril. Res. 43(2): 219-234, June 2018